Deliberative peace referendums - Levy, Ron (Law teacher); O'Flynn, Ian; Kong, Hoi L. (Oxford : Oxford University Press, 2021)
This text investigates the practice of referendums as a method of peacebuilding in conflict societies, their rationales, their successes, and their failures, across a variety of jurisdictions.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 12, 2021).
Keywords: Referendum; Peace-building.; Conflict management